2015
DOI: 10.1002/ps.4024
|View full text |Cite
|
Sign up to set email alerts
|

The degradation rate of thiamethoxam in European field studies

Abstract: CONCLUSION:The degradation rate of thiamethoxam was not significantly affected by application type, cropped fields versus bare soil, soil pH, organic matter content or repeated annual applications. Soil photolysis and leaching were negligible; therefore, calculated DT 50 values were taken to represent microbial degradation. The field degradation rates of thiamethoxam were faster than those previously reported from laboratory degradation studies. They demonstrate that thiamethoxam will degrade to concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 14 publications
3
55
0
1
Order By: Relevance
“…Once applied and within soil, the time required to dissipate 50% of the applied AI (DT 50 ) is highly variable within and between neonicotinoid compounds. The DT 50 of imidacloprid, thiamethoxam, and CLO, the three compounds used in NSTs [3], are 40 [24] to 270 [25], 7.1–92.3 [26], and 277–1386 days [27] respectively under field conditions. There is no published work explaining the high variability in published DT 50 values [21].…”
Section: Introductionmentioning
confidence: 99%
“…Once applied and within soil, the time required to dissipate 50% of the applied AI (DT 50 ) is highly variable within and between neonicotinoid compounds. The DT 50 of imidacloprid, thiamethoxam, and CLO, the three compounds used in NSTs [3], are 40 [24] to 270 [25], 7.1–92.3 [26], and 277–1386 days [27] respectively under field conditions. There is no published work explaining the high variability in published DT 50 values [21].…”
Section: Introductionmentioning
confidence: 99%
“…Field trials performed in Hilton et al . demonstrated a lower geometric mean DT 50 value for seed‐treatment trials versus spray applied trials (25.2 versus 32.5 days), though the effect was not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…The half-life expectancy (t ½ or dissipation time 50% [DT50]) for thiamethoxam and clothianidin has been estimated to range from 7 to 353 d and from 148 to 6931 d, respectively (Wood and Goulson 2017), suggesting a potential for accumulation within the soil, assuming continuous input. However, Hilton et al (2015) reported thiamethoxam DT50s of 7.1 to 92.3 d, with concentrations Published 2019 SETAC wileyonlinelibrary.com/ETC declining to <10% of the initial concentration within 1 yr under field conditions. Given our experimental conditions, the calculated t ½ for thiamethoxam increased with increasing concentration, ranging from 126 d at 1 mg/kg dry soil to 347 d at higher concentrations of 100 mg/kg dry soil; this corresponds with the half-lives of 112 and 134 d reported by de Lima e Silva et al (2018) for 1.1 mg/kg dry soil of thiamethoxam as a pure chemical, and the commercial formulation, Actara, respectively, under similar experimental conditions.…”
Section: Discussionmentioning
confidence: 99%